Development and Validation of RP-HPLC Method for Quantitation of Clarithromycin in Matrix Tablet Dosage Form (Dhaka University Journal of Pharmaceutical Sciences, 2017)
This study was aimed to develop a simple, sensitive and rapid procedure for the analysis of clarithromycin in pure as well as in matrix tablet dosage form by using RP-HPLC method. The chromatographic separation was achieved by a reversed phase C18 column (150 mm length × 4.6 mm i.d., 5 ?m particle size) in an isocratic mode with mobile phase comprising of acetonitrile and 0.035 M potassium dihydrogen phosphate (pH 4.4 ± 0.017) in a ratio of (55: 45, v/v). The eluent was pumped at a flow rate of 0.6 ml/min and the effluent was monitored using UV detector at 210 nm. The method was validated according to the ICH guidelines with respect to linearity, precision, accuracy, selectivity, specificity, ruggedness and robustness. It was found to be linear over the concentration range of 320- 480 ?g/ml (R2= 0.9993) with detection limit of 0.04 ?g/mL. Considering the specifications of this method, the system was found to be suitable for rapid and routine analysis of clarithromycin in pure and matrix tablet dosage form.Dhaka Univ. J. Pharm. Sci. 16(1): 69-75, 2017 (June)